Epidermal SIRT1 regulates inflammation, cell migration, and wound healing. Issue 1 (December 2017) - Qiang, Lei; Sample, Ashley; Liu, Han; Wu, Xiaoyang; He, Yu-Ying
Abstract Sirtuins (SIRT1-7) are NAD-dependent proteins with the enzymatic activity of deacetylases and ADP ribosyltransferases. SIRT1 is the proto member of the proteins in the mammalian sirtuin family and plays multiple roles in aging and disease. Using mice with epidermis-specific SIRT1 deletion, we show that SIRT1 is required for efficient wound healing. SIRT1 deficiency in the epidermis inhibited the regeneration of both the epidermis and the dermal stroma. SIRT1 loss altered the production of many cytokines, inhibited the recruitment of macrophages, neutrophils, and mast cells, the recruitment and activation of fibroblasts, and angiogenesis in the granulation tissue. In keratinocytes, SIRT1 knockdown inhibited EMT, cell migration, and TGF-β signaling. For the first time, using skin-specific mouse model, we demonstrate that epidermal SIRT1 plays a crucial role in wound repair. These findings are novel in understanding how wound healing is regulated. Our findings providein vivo andin vitro evidence that SIRT1 in the epidermis regulates cell migration, redox response, inflammation, epidermis re-epithelialization, granulation formation, and proper wound healing in mice.